AN ANALYSIS OF LEARNING STRATEGIES IN PREPARING FOR THE TOFL TEST OF SIXTH SEMESTER STUDENTS AT UNIVERSITY HKBP NOMMENSEN PEMATANG SIANTAR - Anita Panjaitan; Yanti Kristina Sinaga; Mungkap Mangapul Siahaan (RADJA PUBLIKA, 2025)
This research aimed to described the strategies used by sixth semester students of the English Education Study Program at HKBP Nommensen University, Pematangsiantar, in preparing themselves for the TOEFL test, to see the effectiveness of the strategies used, the obstacles faced in the preparation process, and the correlation described from the strategies used with the scores obtained by students. This research was based on the theory of learning strategies proposed by Cohen and Chamot & O'Malley, which divides learning strategies into three categories, namely metacognitive, cognitive, and social-affective. This research used descriptive qualitative method, with 30 sixth-semester PIA-2 class students at HKBP Nommensen University, Pematangsiantar as the research subjects. Data were collected using an analysis and interactive model proposed by Miles & Huberman, which included data reduction, data presentation, and drawing conclusions. The results of the study indicated that students use various metacognitive strategies (planning, monitoring, evaluation, and time management) as the most dominant strategies, followed by cognitive strategies (practice questions, studying grammar, and reading authentic texts), as well as socio-affective strategies (group discussions, asking for tutor help, and managing anxiety). These strategies had proven effective in improving students' readiness to face the TOEFL test, although their effectiveness varies depending on the consistency and discipline of students in applying them. The main obstacles faced by the students included limited time, difficulty understanding grammar, excessive anxiety before the test, and limited access to learning resources. The conclusion of this research confirms that implementing appropriate, planned, and consistent learning strategies could help students improved their TOEFL preparation and confidence. Using a combination of these three strategies will also help students achieve good scores. However, these strategies need to be tailored to each student's individual circumstances to achieved optimal results.